Investigations of potential non-amino acid SNAT2 inhibitors - Jakobsen, Sebastian; Petersen, Emilie Fynbo; Nielsen, Carsten Uhd (Frontiers in Pharmacology, 2024)
The sodium-coupled neutral amino acid transporter 2 (SNAT2, SLC38A2) has been implicated in cancer for its ability to supply cancer cells with glutamine and sarcosine. A recent high-throughput screen published by Gauthier-Coles et al. (1) identified the non-amino acid 3-(N-methyl (4methylphenyl)sulfonamido)-N-(2-trifluoromethylbenzyl)thiophene-2-carboxamide (MMTC or 57E) as a potent and selective SNAT2 inhibitor. Here we have investigated the ability of MMTC and four other compounds selected from (1) to decrease 3 H-Gly uptake in hyperosmotically treated human prostate cancer PC-3 cells. In these cells, SNAT2 is highly upregulated when the cells are hyperosmotically stressed for 24 hours and is the primary contributor to glycine uptake. The five compounds were investigated at concentrations of 1-50 µM based on their equilibrium solubility. At 37 ºC the equilibrium solubility in HEPES buffered HBSS at pH 7.4 was measured to be 24.9 (53B), 56.1 (54F), 13.3 (55B), and 27.5 (57B) µM, respectively. The equilibrium solubility of MMTC was below the detection limit of the HPLC-UV method, thus less than 1.8 µM. However, a kinetic solubility of approximately 2.5-10 µM could be achieved during the course of the uptake study. In contrast to the previous publication, MMTC showed no inhibition of SNAT2-mediated 3 H-Gly uptake in PC-3 cells at a concentration of 1 or 5 µM, despite a published IC50 of 0.8 µM. Similarly, 53B, 55B, and 57B showed no inhibition at soluble conditions, whereas 54F showed approximately 20 % inhibition at 50 µM. In our experimental setup, the investigated compounds showed limited potential as SNAT2 inhibitors.